ENVIRONMENTAL IMPACT ASSESSMENT IN HYDROPOWER GENERATION: A LIFE CYCLE ASSESSMENT AT PT PLN NUSANTARA POWER UP CIRATA, PURWAKARTA, INDONESIA - Rimala Zahra Wibowo; Suherman; Muhammad Helmi; Arti Hapsari (RADJA PUBLIKA, 2026)
PT PLN Nusantara Power UP Cirata is one of the largest hydropower plants in Indonesia, with an installed capacity of 1.008 MW, and plays a strategic role in supporting national electricity supply security. Although classified as renewable energy, hydropower operations are not entirely free from environmental impacts, including greenhouse gas emissions from biomass decomposition in the reservoir and waste generated from turbine and generator maintenance. This study aims to analyze the environmental impacts of electricity generation using the Life Cycle Assessment method with a cradle-to-gate system boundary. The assessment was conducted using SimaPro 9.5.0.2 with the CML-IA Baseline method, where the functional unit was 1 kWh of electricity. The main hotspot within the cradle boundary is the Cirata Reservoir due to diesel consumption, contributing 1.21E-04 kg CO2-eq/kWh to global warming potential, 2.35E-11 kg CFC-11-eq/kWh to ozone depletion potential, 3.52E-07 kg SO2-eq/kWh to acidification potential, and 3.32E-06 kg PO4-eq/kWh to eutrophication potential. Within the gate boundary, hotspots were identified in the turbine, where used oil contributed 1.91E-05 kg CO2-eq/kWh to global warming potential, turbine oil contributed 2.63E-12 kg CFC-11-eq/kWh to ozone depletion and 3.97E-08 kg SO2-eq/kWh to acidification potential, and the sewage treatment plant contributed 3.49E-07 kg PO4-eq/kWh to eutrophication potential.